UNSUR KOMBINASI PADA VISUALISASI RAGAM HIAS BATIK KLASIK SEMÈN GAYA YOGYAKARTA - Suryo Tri Widodo; G.R. Lono Lastoro Simatupang; R.M. Soedarsono; SP. Gustami (Institut Seni Indonesia Yogyakarta, 2016)
Semèn motifs on classical batik of Yogyakarta style, is a motif which visualize floral form withvarious elements motifs on it. Semèn motifs influenced Hindu-Java and Islamic culture. Influencefrom Islamic culture delivere a few motifs in stylization. From visual aspect, some of elementsmotifs on it visualize combine motifs. It become visual concept characteristic in Islam art includein semèn motifs on classical batik of Yogyakarta style. Visualization of motifs can be hide withcombined elements motifs. Keywords: semèn motifs, Yogyakarta classical batik, combine motifs